2017
DOI: 10.1021/acs.jpcb.7b04111
|View full text |Cite
|
Sign up to set email alerts
|

Accurate Determination of Ion Polarizabilities in Aqueous Solutions

Abstract: We present a novel method for obtaining salt polarizabilities in aqueous solutions based on our recent theory for the refractive index of salt solutions, which predicts a linear relationship between the refractive index and the salt concentration at low concentrations, with a slope determined by the intrinsic values of the salt polarizability and the density of the solution. Here we apply this theory to determine the polarizabilities of 32 strong electrolyte salts in aqueous solutions from refractive index and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(57 citation statements)
references
References 36 publications
(138 reference statements)
1
54
1
Order By: Relevance
“…3, since the order of the ionic radii of the anions follows the order 75 The polarizability of an anion is proportional to its size: larger anions are more polarizable. 74,75 However, the reversed Hofmeister series is not completely followed for PC2N as it has been shown that for PNIPAm that LiNTf 2 acts like a strong kosmotrope for PNIPAm. 50 Nevertheless, LiNTf 2 has the strongest effect for PC2N (Fig.…”
Section: Solution Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…3, since the order of the ionic radii of the anions follows the order 75 The polarizability of an anion is proportional to its size: larger anions are more polarizable. 74,75 However, the reversed Hofmeister series is not completely followed for PC2N as it has been shown that for PNIPAm that LiNTf 2 acts like a strong kosmotrope for PNIPAm. 50 Nevertheless, LiNTf 2 has the strongest effect for PC2N (Fig.…”
Section: Solution Propertiesmentioning
confidence: 99%
“…This is clearly visible from the fact that H 2 PO − than either of the latter ions. 75,77 Thus, anion polarizability cannot be the only determining factor for the strength of interaction between PC3N and the anion in all cases. Na 2 CO 3 (up to 2.0 M) and Na 2 SO 4 (up to 1.8 M) were also tested with PC3N, but no transition was observed, and it is possible that the reversed Hofmeister behavior is not followed for these two salts.…”
Section: Pc3n Becomes Insoluble In Nacl Solution Between 425 M and 4mentioning
confidence: 99%
“…Li et al [28] estimated the polarizability of LiCl, NaCl, NaBr, KBr, and Na2SO4 in mixed solvents (water + acetonitrile and water + ethanol). For this purpose, they extended their model reported in [1,23]. The ion polarizability of Na + , Cl − , and Br − in the mixed solvents was reported.…”
Section: Introductionmentioning
confidence: 79%
“…An et al [1] proposed a theoretical equation to describe the refractive index for binary salt solutions (NaCl, KCl, NaBr, and KBr) and water + acetonitrile + salt solutions at 298.15 K, obtaining good results, particularly at low salt concentrations. Li et al [23] presented a method to estimate the polarizability of the ions from their refractive index in water. This method was based on their previous theoretical equation [1].…”
Section: Introductionmentioning
confidence: 99%
“…[80], we calculate μ CIP , μ SIP , A CIP, and A SIP (Table S3, SI) using data for ionic radii, solvent radii, and polarizabilities from Refs. [81][82][83]…”
Section: + and Baclo 4 +mentioning
confidence: 99%